從儒家式的生命經驗到儒家生命倫理學: From Confucian Life Experience to Confucian Bioethics - CHENG, Guobin (International Journal of Chinese & Comparative Philosophy of Medicine, 2014)
LANGUAGE NOTE | Document text in Chinese; abstract in English only. To reconstruct the Confucian moral tradition, we must first understand the ethical nature of human beings and be fully committed to moral practice. The existing research on the concept of an ethical cure shows how Chinese people understand life, medicine and moral and ethical practice, and explores the possibility of reconstructing the Confucian way of life in modern society. However, too great an emphasis on the connection between ethics-based medical treatment and Confucian cultural identity misrepresents the close relationship between ethics and Confucianism. DOWNLOAD HISTORY | This article has been downloaded 46 times in Digital Commons before migrating into this platform.